2018
DOI: 10.1038/s41427-018-0013-x
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field-induced phase transition and pinched P–E hysteresis loops in Pb-free ferroelectrics with a tungsten bronze structure

Abstract: Antiferroelectrics are of interest due to their high potential for energy storage. Here, we report the discovery of pinched, polarization-vs.-electric field (P-E) hysteresis loops in the lead-free tungsten bronze ferroelectrics Ba 4 Sm 2 Ti 4 Nb 6 O 30 and Ba 4 Eu 2 Ti 4 Nb 6 O 30 , while a broad, single P-E hysteresis loop was observed in the analogue compound Ba 4 Nd 2 Ti 4 Nb 6 O 30 . Pinched P-E loops are similar to antiferroelectric hysteresis loops, but in perovskites, they are mostly caused by an extrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…In a related modelling study, Sheldon and Di Ventra [81] showed that activation of disordered memristive networks with strong memory (G on / G off ≫ 1), with an electrical 'crack' appearance, is consistent with a discontinuous (first-order) phase transition, rather than a continuous (secondorder) transition, which is a hallmark of criticality [82]. First-order phase transitions are indicated by hysteresis and have also been observed in ferroelectrics [83] and in models of spiking neural networks [84]. For a randomly diluted lattice network, the authors also found avalanches with power-law size distributions, similar to that observed in neuronal population cultures [34], with an exponent that converges towards the value predicted by mean-field-theory as network size increases.…”
Section: Network Dynamicsmentioning
confidence: 94%
“…In a related modelling study, Sheldon and Di Ventra [81] showed that activation of disordered memristive networks with strong memory (G on / G off ≫ 1), with an electrical 'crack' appearance, is consistent with a discontinuous (first-order) phase transition, rather than a continuous (secondorder) transition, which is a hallmark of criticality [82]. First-order phase transitions are indicated by hysteresis and have also been observed in ferroelectrics [83] and in models of spiking neural networks [84]. For a randomly diluted lattice network, the authors also found avalanches with power-law size distributions, similar to that observed in neuronal population cultures [34], with an exponent that converges towards the value predicted by mean-field-theory as network size increases.…”
Section: Network Dynamicsmentioning
confidence: 94%
“…This backswitching event occurs against an increasingly large electric field with increasing temperature, which indicates increased stability of the disorder with increasing thermal energy. Similar pinched loops in Ba 4 Sm 2 Ti 4 Nb 6 O 30 and Ba 4 Eu 2 Ti 4 Nb 6 O 30 filled TTBs (and later in Ba 4 Sm 2 Fe 0. 5 Ti 3 Nb 6.5 O 30 ) have recently been shown to coincide with a field-driven incommensurate to commensurate transition using in situ electron diffraction.…”
Section: Introductionmentioning
confidence: 55%
“…The observed peak splitting in J–E loops could be due to the coexistence of the polar and non-polar phases, which reversibly switch by applying the electric field. 53–55 In addition, Fig. 6c illustrates the room-temperature bipolar S–E plots of the x BTSn samples.…”
Section: Resultsmentioning
confidence: 99%